Murine models for studying treatment, prevention and pathogenesis of FNAIT. (February 2020) - Rasmussen, Trude Victoria; Ahlen, Maria Therese
Abstract: Maternal alloimmunization to paternally inherited antigens on fetal/neonatal platelets can cause fetal/neonatal alloimmune thrombocytopenia (FNAIT) after antibody-mediated removal of platelets from the fetal circulation. The complications vary from mild bleeding symptoms to severe intracranial hemorrhage and subsequent neurological impairment or death. Studies on in vivo mechanisms are challenging to measure directly in pregnant women, rendering murine models as valuable and attractive alternatives, despite some critical differences between mice and men affecting the translational value. Here we present and discuss, the different murine models that substantially have increased our knowledge and understanding of FNAIT pathogenesis – as well as pre-clinical evaluation of therapeutic and preventive strategies.